Assessment of Right Heart Functions in Children with Mild Cystic Fibrosis - Guliyeva, Aynur; Cakir, Erkan; Yazan, Hakan; AlShadfan, Lina; Sharifov, Rasul; Temur, Hafize Otcu; Karaarslan, Utku; Yozgat, Can Yilmaz; Erenberk, Ufuk; Yakut, Kahraman; Yozgat, Yilmaz (Klinische Pädiatrie, 2021)
Background Cystic fibrosis (CF) is a multisystemic disease that prevalently involves the lungs. Hypoxemia occurs due to the existing of progressive damage to the pulmonary parenchyma and pulmonary vessels. The condition may cause systolic and diastolic dysfunction to the right ventricle due to the effects of high pulmonary artery systolic pressure (PASP). The study aimed to determine echocardiographic alterations in PASP, right ventricle (RV) anatomy, and functions in mild CF children.Materials and Methods RV anatomy, systolic, and diastolic functions were evaluated with conventional echocardiographic measurements. Estimated PASP was used measured with new echocardiographic modalities, including pulmonary artery acceleration time (PAAT), right ventricular ejection time (RVET), and their ratio (PAAT/RVET). The obtained echocardiographic data were statistically compared between the patient group and the control group.Results The study consisted of 30 pediatric patients with mild CF and 30 healthy children with similar demographics. In patient group, conventional parameters disclosed differences in RV anatomy, both systolic and diastolic functions of RV compared with the healthy group. We did not compare the patient group with published standard data because of the wide range variability. However, new echocardiographic parameters showed notable increase in pulmonary artery pressure compared with values of control group and published standard data (p<0.001).Conclusion Elevated PASP, RV failure, and Cor pulmonale usually begin early in children with mild CF. In addition to routine echocardiographic measurements to evaluate RV, we recommend the use of new echocardiographic modalities for routine examinations and in the follow up of children with mild CF.
Keywords: Cystic fibrosis; Pulmonary hypertension; Pulmonary function test; Cor Pulmonale; Childhood Age Group